Between Fiqh and Falak: Legal Authority and Scientific Evidence in the Formulation of MUI Fatwas on Qibla Direction in Indonesia - Darlius Darlius; Ridhokimura Soderi (AL-MUTSLA, 2026)
This research aims to provide a critical legal analysis of the epistemic tensions, methodological gaps and negotiations of authority within two fatwas issued by the Indonesian Ulema Council (MUI) No. 3/2010 and its subsequent correction and rapid amendment in Fatwa No. 5/2010 concerning the determination of the direction of the qibla in Indonesia. Employing a normative legal research method with a critical legal studies approach, this study deconstructs the textual formulation of these fatwas by applying the ushul fiqh theory of tahqiq al-manat (verification of the locus of law) alongside a framework of epistemic authority to evaluate the integration of scientific evidence in the formulation of modern Islamic law. The results of this analysis show that Fatwa No. 3/2010 suffers from an epistemological flaw due to the use of rigid legal formalism, which isolates the text from spatial-empirical reality. The emergence of Fatwa No. 5/2010 reveals an institutional defence mechanism that synthetically re-justifies classical texts under scientific pressure. This study demonstrates that modern astronomy has shifted the locus of the qibla from the realm of speculation (zanni) to that of absolute empirical certainty (qath’i), thereby redefining the operational boundaries of tahqiq al-manat. Consequently, this study proposes an integrative and inclusive model for contemporary ifta’ methodology. This study recommends the structural institutionalisation of scientific expertise within fatwa commissions, shifting the approach from a reactive-comparative model to an interdisciplinary-organisational framework capable of responding to the scientific disruptions of the 21st century.